Wacana Hermeneutika dan Implikasinya Terhadap Teks Keagamaan - Zaprulkhan, Zaprulkhan (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2016)
Hermeneutics discourse relates to the interpretation of texts. Hermeneutic interprets literal, social, and religious text. In the classic history, man actually had been in contact with the name of interpretation (hermeneutics) naturally. However, hermeneutics was formulated methodically and theoretically at the beginning of the 19th century. Hermeneutics was not seen as an understanding of free, non-definitive, but as a method of reading, understanding and interpretation in a wide area. Likewise texts are highlighted by a hermeneutic not only written texts, including the scriptures, but also social texts, such as socio-cultural phenomenon. This article will photograph developments in hermeneutics and the three typologies of contemporary hermeneutics, namely hermeneutical theory, philosophical hermeneutics, and critical hermeneutics. In the end of this paper, it is going to give a conclusion which depicts hermeneutics contribution in the method of interpretation of religious text that opens the meaning productively.